THE PROBLEMATIZATION METHODOLOGY USED BY NURSES IN ADOLESCENTS SEXUAL EDUCATION - Juliana Balbinot Reis Girondi; Simone Cristine dos Santos Nothaft; Franciole Maria Bridi Mallmann (Universidade Federal do Paraná, 2006)
It is an experienced account on sexual education with adolescents from Public Schools of a country town in Santa Catarina State/ Brazil. It was used, as theoretical background, the problem-solving methodology. In order to do that, some methodological steps have been followed: reality observation and study case definition, key aspects, theorizing, solution hypotheses and reality application. Thus, promoting actions have been developed in relation to adolescents' health, focusing on their sexuality, absorbing their experiences and fostering their growth and whole development.